Peran Self-Confidence Terhadap Keberanian dan Kompetensi Public Speaking - Damianus Alung; Muhammad Ramzah; Najwa Risqina Usman (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Public speaking is an essential communication skill for university students, especially those studying communication and multimedia, as it supports academic performance and professional readiness. Nevertheless, many students still experience anxiety and lack confidence when speaking in public. This study aims to examine the role of self-confidence in supporting students’ public speaking abilities at the Faculty of Communication and Multimedia, Universitas Mercu Buana Yogyakarta. This research employed a quantitative approach with a descriptive survey design. Data were collected through an online questionnaire distributed to students and measured using a four-point Likert scale. The study focused on self-confidence and social learning as factors related to public speaking activities. Descriptive statistical analysis was used to identify response patterns and tendencies. The findings indicate that self-confidence plays an important role in shaping students’ courage and effectiveness in public speaking. Students with higher levels of self-confidence tend to feel more comfortable speaking in public, demonstrate better emotional control, and communicate ideas more clearly. These results emphasize the importance of fostering self-confidence through supportive learning environments and continuous public speaking practice in higher education.